The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2147/ijn.s164228
|View full text |Cite
|
Sign up to set email alerts
|

Novel nanocrystal-based solid dispersion with high drug loading, enhanced dissolution, and bioavailability of andrographolide

Abstract: ObjectiveThe current study sought to design a quickly dissolving, high drug loading nanocrystal-based solid dispersion (NC-SD) in order to improve the dissolution of poorly soluble drugs.MethodsThe NC-SD was prepared by means of combination of homogenization and spray-drying. Polymer hydroxypropylmethylcellulose (HPMC) was used as baseline dispersant for NC-SD of the model drug – andrographolide (AG). Three superdisintegrants cohomogenized with HPMC were used as codispersant for AG-NC-SD and compared to common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…As depicted in Figure 3a, AG's diffraction pattern was highly crystalline in its natural state, as indicated by the numerous peaks. The results resemble those of Ma et al [19]. The powdered PVP K30 was amorphous where no prominent peaks were detected ( Figure 3b).…”
Section: Powder X-ray Diffraction Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…As depicted in Figure 3a, AG's diffraction pattern was highly crystalline in its natural state, as indicated by the numerous peaks. The results resemble those of Ma et al [19]. The powdered PVP K30 was amorphous where no prominent peaks were detected ( Figure 3b).…”
Section: Powder X-ray Diffraction Analysissupporting
confidence: 88%
“…Various formulations have been proposed to improve the solubility, dissolution, and bioavailability of AG. These formulation approaches for AG included solid dispersion (SD) [16][17][18][19][20], liposomes [21], niosomes [22], and solid lipid nanoparticles (SLN) [23] and focused on in vitro characterization for delivery systems and assessing their effects on diverse cell models. The inclusion complex composed of AG and hydroxypropyl-β-cyclodextrin has been proposed to elevate the bioavailability of AG by 1.6-fold [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing with the oral administration of pure ADG, we found that the mean C max and AUC values of ADG for ADG‐Soluplus solid dispersion were approximately increased 1.96‐ to 2.53‐fold, confirming the superiority of Soluplus as ADG solid dispersion carrier owing to the strong binding affinity between ADG and Soluplus. Compared to other ADG solid dispersions, the ADG‐Soluplus solid dispersion 1:7 had significant high oral bioavailability . Other solid dispersion, including ADG‐PEG 6000, ADG‐PVP VA64, and ADG‐F68, showed little effect on AGD absorption.…”
Section: Resultsmentioning
confidence: 94%
“…Solid dispersion is designed as drug dispersion system that drug is highly dispersed in a suitable solid carrier, which can effectively change drug physical state from crystalline to amorphous phase owing to the advantages of carriers in enlarging area surface and interacting with drug molecules . Many polymers, such as polyoxyethylene pyrrolidone K30, polyethylene glycol, Eudragit series, hydroxy propyl cellulose, poloxamer, and Soluplus, have been considered as excipients for forming solid dispersion.…”
Section: Introductionmentioning
confidence: 99%